Drug Delivery Nanoparticles: Toxicity Comparison in Retinal Pigment Epithelium and Retinal Vascular Endothelial Cells. (3rd March 2016) - Lin, Haijiang; Yue, Yueran; Maidana, Daniel E.; Bouzika, Peggy; Atik, Alp; Matsumoto, Hidetaka; Miller, Joan W.; Vavvas, Demetrios G.
ABSTRACT: Multiple synthetic polymer nanoparticles (NPs) have been widely used as drug delivery systems. However, their toxicity to the retinal pigment epithelium and retinal endothelium remains unclear. In this study, we analyze the cytotoxic effects of three different kinds of NPs, made of poly lactic-co-glycolic acid (PLGA), polycaprolactone (PCL), and PEGylated PLGA (PEG-PLGA), in a retinal pigment epithelium cell line (ARPE-19) and in primary human retinal vascular endothelial cells (RVEC). PEG-PLGA NPs presented the lowest cytotoxicity on ARPE-19 cells and RVEC as assessed by MTT viability assay. While PLGA and PCL exhibited variable amounts of toxicity, no significant toxicity was observed when incubating cells with high PEG-PLGA concentrations (100 µg/ml), for up to 6 days. On both transmission electron microscopy and confocal microscopy, Rhodamine 6G-loaded PEG-PLGA NPs were observed intracellularly in multiple subcellular organelles. PEG-PLGA NPs are a potentially viable option for the treatment of eye diseases.